Online Retailer’s Understanding of Consumers While Offering the Product: A Narrative Study - Thakur, Ritesh Kumar (International Research Journal of Parroha, 2023)
Prior research in the field of online retail has predominantly adopted a consumer-centric perspective, primarily rooted in the positivist paradigm. While these studies have shed light on consumer needs, values, website design, and the role of content, there has been a notable dearth of literature that explores the online retailer's narrative, their lived experiences, and their interactions while offering products to consumers. This study seeks to address this gap by employing a narrative approach to data collection and analysis. In this study, a narrative approach was employed to understand the experiences and perspectives of online retailers. Qualitative data collection methods were used to delve into the stories and experiences of these retailers, going beyond the traditional consumer-focused investigations. The findings of this research reveal intriguing insights into the practices of online retailers. It becomes evident that online retailers may, at times, hide or manipulate information to serve their vested interests, particularly when it comes to designing content for product offerings. Their narratives indicate the challenges they face in cultivating trust among consumers, retaining their customer base, and providing satisfactory after-sales services. However, online retailers are not passive actors; they employ a variety of strategies to effectively communicate product attributes and enhance customer retention. This research sheds light on the complex interplay of interests, strategies, and challenges within the online retail space, from the perspective of the retailers themselves.